Institutional investors ownership and firm value: evidence from Malaysia / Nurul Azlin Azmi …[et al.] - Azmi, Nurul Azlin; Abd Sata, Fazrul Hanim; Abdullah, Norhidayah; Ab Aziz, Noor Hidayah; Ismail, Ida Suriya (Accounting Research Institute (ARI), 2021)
Institutional investors play a significant role as an external watchdog to promote good governance to uphold firm value. The existence of institutional investors as shareholders is able to reduce the agency problem and the costs that arise from shareholder-manager relationship. This study aimed to examine the influence of institutional investors’ shareholdings and firm value among public listed firms in Malaysia. Specifically, it is argued that only pressure-insensitive institutional investors play an active monitoring role to increase a firm’s value, while pressure-sensitive investors, do not. This study employed 595 public listed firms from the main market in Bursa Malaysia for the period 2013 to 2017 (2795 firm-year observations). The results show that the pressure-sensitive and pressure-insensitive investors are positively significant to a firm’s value. These findings revealed that institutional investors in Malaysia play a significant role in increasing a firm’s value. This study will have a significant contribution to firms and the academic literature which states that all types of institutional investors in Malaysia are effectively monitoring their roles as an external corporate governance watchdog. The existence of these investors will be able to promote better governance and increase a firm’s value.